The relationship between perceived teachers' self-disclosure and out-of-classroom communication among Malaysian undergraduates in a private institution of higher learning / Aniljeet Singh, Paul Gnanaselvam Pakirnathan and S. Maartandan Suppiah - Singh, Aniljeet; Pakirnathan, Paul Gnanaselvam; Suppiah, S. Maartandan (UiTM Press, 2018)
This quantitative study was conducted to determine whether a significant relationship exists between perceived teachers' self-disclosure and students' out of classroom communication with teachers in a Malaysian private institution of higher learning. A survey consisting of two questionnaires, namely the Perceived Teacher's Self-Disclosure scale designed by Cayanus and Martin (2008) as well as Knapp and Martin's (2002) Out-of-Classroom Communication Scale were collected from 144 final year undergraduates from a Malaysian private institution of higher learning. Using the SPSS, the Pearson product-moment correlation coefficient, independent-samples t-test and one-way between-groups ANOVA with post-hoc tests were used to analyze the data. The findings indicated a positive relationship between the dimensions of amount and relevance in perceived teachers' self-disclosure and students' out of classroom communication. There was no significant difference recorded between gender, with perceived teachers' self-disclosure and students' out of classroom communication. Besides, there was also no significant difference recorded between age, with perceived teachers' self-disclosure and students' out of classroom communication. The study concludes that Malaysian undergraduates' perceptions towards teachers' self-disclosure influences the out of classroom communication with teachers.